Outcome of Nonketotic Hyperglycinemia in Lebanon: 14-Year Retrospective Review - Shbarou, Rolla M.; Boustany, Rose Mary; Daher, Rose T.; Pakdel, Parisa; Noureddine, Abir; Karam, Pascale E. (Neuropediatrics, 2019)
Nonketotic hyperglycinemia is a rare inborn error of glycine metabolism characterized by a severe metabolic encephalopathy with drug-resistant seizures. Here, we report the outcome of nonketotic hyperglycinemia in a cohort of patients diagnosed and followed-up at a tertiary care reference center in Lebanon, between 2000 and 2014.Eight out of 12 patients with nonketotic hyperglycinemia were retrospectively reviewed. The remainders were excluded for incomplete data. The majority of cases presented with seizures and hypsarrhythmia or burst suppression patterns. Half of the patients died. Survival varied between 7 days and 18 years. Seizures remained unresponsive with poor outcome, despite standard supportive care and antiepileptic therapy; however, two patients were responsive to ketogenic diet and one of them became seizure-free.Scarce data on the outcome of nonketotic hyperglycinemia patients from the Middle East and North Africa region are available. The ketogenic diet, in combination with standard therapies, appears to be effective in controlling the seizures in this devastating disorder. Larger multicenter studies are still needed to establish the role of the ketogenic diet in nonketotic hyperglycinemia.
Keywords: nonketotic hyperglycinemia; ketogenic diet; infantile spasms; hypsarrhythmia; burst suppression pattern; MENA region